What makes a beverage healthy? A qualitative study of young adults' conceptualisation of sugar-containing beverage healthfulness. (1st July 2020) - Brownbill, Aimee L.; Braunack-Mayer, Annette J.; Miller, Caroline L.
Abstract: Sugar-containing beverages are the leading source of added sugar consumption among young adults. The aim of this study was to explore how young adults conceptualise what influences the healthfulness of sugar-containing beverages. Seven focus groups stratified by gender and educational institute were conducted with South Australians aged 18–25 years (n = 32). Focus groups were semi-structured and included a ranking activity where participants individually ranked eight beverages from least to most healthy. Focus groups were recorded, transcribed verbatim and thematically analysed. Participants commonly selected soda (soft drink) and energy drink as the least healthy beverage and water as the healthiest, but those between varied in rankings. Four themes were identified relating to how participants conceptualise beverage healthfulness in the thematic analysis: ingredients harmful to health, properties beneficial to health, functionality, and packaging. While participants were aware that beverages can contain high amounts of sugar, and that this can be harmful to health, many other factors influence the perceptions of beverage healthfulness and these can outweigh the perceived harms of consumption. Public health interventions and policies are needed to address misperceptions about the healthfulness of sugar-containing beverages to better put the harms of high sugar consumption in perspective for consumers.